Print culture and the medieval author : Chaucer, Lydgate, and their books 1473-1557 - Gillespie, Alexandra (Oxford English monographs., 2006)
Alexandra Gillespie takes a new look at hundreds of neglected old books containing works by Chaucer, the 'father' of English poetry, and his much-maligned follower, John Lydgate. She demonstrates that the shift from manuscript to print was part of the controversial process by which Chaucer earned his exclusive place in English literary history. - ;Print Culture and the Medieval Author is a book about books. Examining hundreds of early printed books and their late medieval analogues, Alexandra Gillespie writes a bibliographical history of the poet Geoffrey Chaucer and his follower John Lydgate.